2013
DOI: 10.1093/eurheartj/eht184
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cardiac magnetic resonance imaging on human lymphocyte DNA integrity

Abstract: AimsMagnetic resonance (MR) imaging is widely used for diagnostic imaging in medicine as it is considered a safe alternative to ionizing radiation-based techniques. Recent reports on potential genotoxic effects of strong and fast switching electromagnetic gradients such as used in cardiac MR (CMR) have raised safety concerns. The aim of this study was to analyse DNA double-strand breaks (DSBs) in human blood lymphocytes before and after CMR examination.Methods and resultsIn 20 prospectively enrolled patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 30 publications
5
59
1
2
Order By: Relevance
“…We also reported, for the first time, the dynamic evolution of DNA damage over long-time periods (≤1 month). Fiechter et al 11 showed significant DNA damage in patient T lymphocytes as soon as 1 or 2 hours post contrast enhanced CMR. …”
Section: Cmr Scanning and Dna Damage Of Circulating Lymphocytesmentioning
confidence: 98%
See 2 more Smart Citations
“…We also reported, for the first time, the dynamic evolution of DNA damage over long-time periods (≤1 month). Fiechter et al 11 showed significant DNA damage in patient T lymphocytes as soon as 1 or 2 hours post contrast enhanced CMR. …”
Section: Cmr Scanning and Dna Damage Of Circulating Lymphocytesmentioning
confidence: 98%
“…[11][12][13][14] We showed that γ-H2AX intensity in NK cells could be a more sensitive marker than T lymphocytes to evaluate early CMR-induced DNA damage. We also reported, for the first time, the dynamic evolution of DNA damage over long-time periods (≤1 month).…”
Section: Cmr Scanning and Dna Damage Of Circulating Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…This would support why the authors found a delay between CMR exposure and DNA damage. The authors suggest that previous studies had found a somewhat earlier increase in DSB because patients were also exposed to gadolinium, 3,23 which has been shown to potentiate the genotoxic effect of CMR 30 but still requires some delay after CMR exposure.…”
Section: See Article By Lancellotti Et Almentioning
confidence: 90%
“…However, some genotoxic effects of MRI scanning have been demonstrated under in vivo as well as in vitro conditions (Suzuki et al, 2001;Simi et al, 2008;Lee et al, 2011;Fiechter et al 2013). A recent review on safety of MRI has recommended a need for further studies as a precautionary principle (Hartwig et al, 2009).…”
Section: Genotoxic Effectsmentioning
confidence: 99%